Penerapan Metode Pembelajaran Kooperatif Tipe Tai (Team Accelerated Instruction) dalam Pembelajaran Membaca Bahasa Jerman Siswa Kelas XI IPA 2 SMAN 8 Kediri - FEBRIANTI, PRISKA (LATERNE, 2013)
Reading is animportant skill learning a language. But there are a lot of Problems in Reading. Student think that reading is boring. When they read a text, they are difficult to understand. Therefore, educators need to implement various methods which can improve students' reading. One of the methods applied is the type of Cooperative Learning TAI (Team Accelerated Instruction) class XI science 2 SMAN 8 Kediri" The problem in this Research are : (1) How are the application of Cooperative Learning Method type TAI (Team Accelerated Instruction) in learning to read German language class XI science 2 SMAN 8 Kediri?, (2) How are the results of student class XI science 2 SMAN 8 Kediri with implementing Cooperative Learning Methods TAI (Team Accelerated Instruction) in learning to read German Language ? This Research aims to: (1) describe the application of Cooperative Learning Method type TAI (Team Accelerated Instruction) in learning to read German language class XI science 2 SMAN 8 Kediri.(2) Knowing the results of student class XI science 2 SMAN 8 Kediriafter Implementing Cooperative Learning TAI (Team Accelerated Instruction)) in learning to readGerman Language ?. This research is a combination of qualitative and quantitative descriptive. Instruments of this researchareObservation’s Sheet and Test. The research data are the result of Observation’s Sheet and Test. (1) Observation’s Sheet contains of student activity during the process of learning to read German language implementing cooperative learning type of TAI (Team Accelerated Instruction). The data were analyzed with a formula to determine the percentage increase. The result is the overall frequency of 87,5% of student activity and includes criteria very well, because it is worth the four highest scores by the number of 50%. (2) Tests are Pre-Test and Post Test. Furthermore, the data were analyzed using T-test test. T-test of the test results obtained, namely t-count = 5.1 while the t-table = 2.03. Since t calculated> t-table (5.1> 2.03), meaning there is a positive and significant correlation between pre-test and post-test. So the implementation of cooperative learning method type TAI (Team Accelerated Instruction) can improve student learning outcomes XI science 2 SMAN 8 Kediri in learning to read German. The conclusion of this study is the Cooperative Learning Method TAI (Team Accelerated Instruction) can improve reading skills and students learning outcomesclass XI science 2 SMAN 8 Kediri Typeof cooperative learningmethodsTAI(TeamAcceleratedInstruction) can be used as an alternativemethod oflearning to readGerman language. In addition,this methodshouldbe applicable tootherlanguage skills, such as writing, speaking, and listening. Keywords:Reading, Cooperative Learning Type TAI (Team Accelerated Instruction)